Lyle, Lyle, crocodile [videorecording (DVD)] - Davies, William (Screenwriter); Bardem, Javier, 1969-; Wu, Constance, 1982-; Fegley, Winslow; McNairy, Scoot; Gelman, Brett, 1976-; Nwodim, Ego, 1988-; Pasek, Benj; Paul, Justin, 1985-; Margeson, Matthew, 1980-; Aguirresarobe, Javier, 1948-; Waber, Bernard (Sony Pictures Home Entertainment, 2022)
It's hard enough to adjust to a big move -- even harder when it's to New York City -- and harder still when there's a singing crocodile living in your attic! Josh Primm isn't making friends easily, so he's glad that Lyle is willing, but their menacing neighbor is determined to rid the neighborhood of the reptile.